Lactic Acid Production From Broken Rice Via Fermentation Process - Baharuddin, Nur Shuhada (Universiti Sains Malaysia, 2020)
One of the consequences of industrial food production activities is the generation of high volumes of waste, whose disposal can be problematic, since it occupies large spaces and when poorly managed can pose environmental and health risks for the population. The rice industry is an important activity and generates large quantities of waste. The main solid waste generated in the rice production cycle is broken rice. Broken rice refers to the fragments of rice grain obtained by milling and separated after the polishing phase. It has the same chemical composition as white rice and its most important components are carbohydrates. The aim of this research is to investigate the optimum condition and potential of utilizing fermented broken rice to the production of lactic acid using different strain of bacteria culture.